Netnography the essential guide to qualitative social media research - Kozinets, Robert (SAGE, 2020)
Machine generated contents note: 1.Introducing: Netnography, Qualitative Social Media Research Methods, and This Book -- 2.A History of Social Media -- 3.Media: Communicating and Connecting in the 21st Century -- 4.Socialities: All the Ways We Connect -- 5.Praxis: Introducing Practices and Data Operations -- 6.Ethics: Procedures and Flowcharts, Updates and Rules -- 7.Data: The Methodology of Netnographic Data Collection -- 8.Investigating: J Five Steps to Social Media Data Collection -- 9.Interacting: Turning Connection and Communication into Research Data -- 10.Immersing: Journaling and Organizing a Reflective Curation -- 11.Integrating: Combining Telescopic and Microscopic Understandings -- 12.Analyzing: Elemental Data Transformation Operations -- 13.Interpreting: How to Discover and Make Meaning from Netnographic Data -- 14.Communicating: Presenting and Publishing Your Netnography -- 15.The Future of Netnography.